The effect of child development on the components of the Frequency Following Response: Child development and the Frequency Following Response - Ferreira, Laís; Pinto, Julia Dalcin; Temp, Déborah Aurélio; Broman, Eli Natáli; Skarzynski, Piotr H.; Skarzynska, Magdalena B.; Moraes, Denis Altieri De Oliveira; Sanfins, Milaine Dominici; Biaggio, Eliara Pinto Vieira (PloS one, 2022)
During childhood, neuronal modifications occur so that typical childhood communicative development occurs. This work aims to contribute to the understanding of differences in the speech encoding of infants and school-age children by assessing the effects of child development, in different phases of early childhood, on the encoding of speech sounds. There were 98 subjects of both sexes, aged from 1 day to 8 years and 9 months who participated in the study. All subjects underwent a Frequency Following Response (FFR) assessment. A regression and linear correlation showed the effects of age in the FFR components, i.e., significant decrease in the latency and increased amplitude of all FFR waves with age. An increase in the slope measure was also observed. Younger infants require more time and show less robust responses when encoding speech than their older counterparts, which were shown to have more stable and well-organized FFR responses.